A Psychometric Evaluation of the Danish Version of the Theory of Mind Storybook for 8–14 Year-Old Children - Clemmensen, Lars; Bartels-Velthuis, Agna A.; Jespersen, Rókur av F.; van Os, Jim; Blijd-Hoogewys, Els M. A.; Ankerstrøm, Lise; Væver, Mette; Daniel, Peter F.; Drukker, Marjan; Jeppesen, Pia; Jepsen, Jens R. M. (Frontiers in Psychology, 2016)
Abstract Background Theory-of-Mind (ToM) keeps on developing in late childhood and early adolescence, and the study of ToM development later in childhood had to await the development of sufficiently sensitive tests challenging more mature children. The current study aimed to investigate the psychometric properties of the Danish version of the Theory-of-Mind Storybook Frederik (ToM-Frederik). Methods We assessed whether ToM-Frederik scores differed between a group of 41 typically developing (TD) children and a group of 33 children with High functioning Autism Spectrum Disorder (HFASD). A lower mean ToM-Frederik score was expected in the HFASD group. To determine the convergent validity of ToM-Frederik, potential associations with Strange Stories and Animated Triangles (AT) were analyzed. Furthermore, potential associations between ToM-Frederik and the Social Responsiveness Scale (SRS) and between ToM-Frederik and the Social Emotional Evaluation (SEE) Total score were analyzed. Results A significantly higher ToM-Frederik score was observed in the TD group compared to the HFASD group. Furthermore, the convergent validity of ToM-Frederik as a measure of ToM was supported by significant and positive associations with the Strange Stories and the AT scores in the HFASD group, whereas ToM-Frederik was significantly correlated with Strange Stories, but not with AT in the TD group. ToM-Frederik was not significantly associated with SRS in neither the HFASD nor the TD group. Conclusion The findings are supportive of ToM-Frederik as a valid indicator of deficits at the group level in children with HFASD between 7 and 14 years of age. Furthermore, the convergent validity is supported.